MAPPING OF MANGROVE ZONING AND ITS RELATIONSHIP WITH SALINITY IN THE CIJILANG RIVER FLOW, PANGANDARAN REGENCY - Firdaus, Reinaldy (Jakarta Technical University of Fisheries, 2025)
This study aims to map mangrove zoning and its relationship with salinity along the Cijulang River flow, Pangandaran Regency. The method used is a survey with a quantitative approach using purposive sampling techniques, focused on analyzing the structure of mangrove communities through important value indices (INP), diversity indexes, Evenness indices, and dominance indices. The results of the study showed that there were six species of mangroves, namely Aegiceras corniculatum, Avicennia marina, Bruguiera gymnorrhiza, Nypa fruticans, Sonneratia alba, and Rhizophora mucronata. Mangrove zoning is divided into three, namely the open zone (Station I, Batukaras Village), the central zone (Stations II and III), and the land zone (Station IV, Kondangjajar Village). Sonneratia alba has the highest INP value of 87%, while Bruguiera gymnorrhiza has the lowest INP value of 10%. Overall, the results of the study show that the community structure and mangrove zoning pattern in the Cijulang River are related to variations in the salinity level of the waters, sequentially found mangrove vegetation at high salinity values (6,3 ppt) to low (3 ppt) starting with the species Avicennia marina, Rizophora mucronata, Sonneratia alba, Aegiceras corniculatum, Bruguiera gymnorrhiza and Nypa fruticans.